New Genetic Analysis in Cases with Hunter Syndrome in Whom IDS Gene Mutations Could Not Be Detected: RNA Sequencing - Akgun, Abdurrahman; Ergin, Bora; Bilgin, Huseyin; Ceylaner, Serdar (Briefland, 2023)
Introduction: Mucopolysaccharidosis-II (MPSII) is diagnosed based on a deficiency in iduronate 2-sulfatase enzyme activity. Detection of a hemizygous pathogenic variant in the iduronate 2-sulfatase (IDS) gene confirms the diagnosis in a male proband. Case Presentation: We report a five-year-old boy with MPSII in whom no mutation was detected in the IDS gene by next-generation sequencing (Miseq-Illumina) covering the coding regions of the gene. Therefore, we tried to detect the mutation in the IDS gene using RNA sequencing that has recently been used. Conclusions: In some diseases diagnosed by clinical and biochemical methods, mutations cannot be detected even with advanced genetic methods, such as next-generation sequencing. In these cases, we emphasize that mutations should be investigated using other methods, including RNA sequencing.
Keywords: Hunter Syndrome; Next-Generation Sequencing; RNA Sequencing